Suplementasi Probiotik (Lactobacillus plantarum) dalam Sari Buah Sebagai Alternatif Produk Pangan Fungsional - Ernanin Dyah Wijayanti Ambar Fidyasari Fitri Eka Lestari (Universitas Muhammadiyah Malang, 2012)
Most of probiotic product as functional food were developed from dairy product. However, milk protein content cause allergy and make it limited to non vegetarians only. To solve these problems, some efforts were tried to produce probiotic drink from fruit juice, such as pineaple, tomato, papaya and aple. The aims of this research were to know the quality of probiotic fruit juice organoleptically and the viability of probiotic in it. Lactobacillus plantarum were used as probiotic and the fermentation process were last for 5 days at 30°C. The results showed that the best quality performed by fermented aple juice, with sour taste, pale brown color, aple fermented aroma and good homogenity. The probiotic viability also showed highest number, 1,7x108 cfu/ml. This research can be developed to produce fermented fruit juice with better quality.